Does social media presence of luxury brands affect consumers´ perceived luxury value? - Rozwadowska, Aleksandra Katarzyna (2021)
Social media has fundamentally transformed the business environment. In fact, in most industries social media adoption has been relatively rapid, however, luxury brands’ relationship with social media is slightly more complicated. The appeal of luxury products stems from their prestige and exclusivity. This is not the case for social media platforms. They pose both a challenge and an opportunity for luxury sector. Hence objective of this study is to investigate whether social media presence of luxury brands affects consumers’ perceived luxury value. Through an experimental research design and quantitative data collection, results show that the former has little to no effect on the latter.